The mechanism of functional up-regulation of P2X3 receptors of trigeminal sensory neurons in a genetic mouse model of familial hemiplegic migraine type 1 (FHM-1). - Swathi K Hullugundi; Michel D Ferrari; Arn M J M van den Maagdenberg; Andrea Nistri (PLoS ONE)
A knock-in (KI) mouse model of FHM-1 expressing the R192Q missense mutation of the Cacna1a gene coding for the α1 subunit of CaV2.1 channels shows, at the level of the trigeminal ganglion, selective functional up-regulation of ATP -gated P2X3 receptors of sensory neurons that convey nociceptive signals to the brainstem. Why P2X3 receptors are constitutively more responsive, however, remains unclear as their membrane expression and TRPV1 nociceptor activity are the same as in wildtype (WT) neurons. Using primary cultures of WT or KI trigeminal ganglia, we investigated whether soluble compounds that may contribute to initiating (or maintaining) migraine attacks, such as TNFα, CGRP, and BDNF, might be responsible for increasing P2X3 receptor responses. Exogenous application of TNFα potentiated P2X3 receptor-mediated currents of WT but not of KI neurons, most of which expressed both the P2X3 receptor and the TNFα receptor TNFR2. However, sustained TNFα neutralization failed to change WT or KI P2X3 receptor currents. This suggests that endogenous TNFα does not regulate P2X3 receptor responses. Nonetheless, on cultures made from both genotypes, exogenous TNFα enhanced TRPV1 receptor-mediated currents expressed by a few neurons, suggesting transient amplification of TRPV1 nociceptor responses. CGRP increased P2X3 receptor currents only in WT cultures, although prolonged CGRP receptor antagonism or BDNF neutralization reduced KI currents to WT levels. Our data suggest that, in KI trigeminal ganglion cultures, constitutive up-regulation of P2X3 receptors probably is already maximal and is apparently contributed by basal CGRP and BDNF levels, thereby rendering these neurons more responsive to extracellular ATP.